Pengaruh Komposisi Tepung Wortel (Daucus Carota L) dan Tepung Terigu terhadap Karakteristik Mie Kering - Florensia Angelika; Almaria Heliana; Yuyun Wahyuni (Fakultas Pertanian, Universitas Nusa Nipa, 2024)
The study entitled “The Effect of Carrot Flour and Wheat Flour Composition on the Characteristics of Dried Noodles” aims to determine the effect of the composition of carrot flour and wheat flour on the characteristics of dried noodles and to identify the best proportion of carrot flour and wheat flour to produce the best dried noodles. This study used a Completely Randomized Design (CRD) with one factor, namely the composition of carrot flour and wheat flour on the characteristics of dried noodles. The experiment consisted of five treatment levels, and each formulation was repeated four times, resulting in 20 experimental units. The treatments were: F0 (0% carrot flour and 100% wheat flour), F1 (10% carrot flour and 90% wheat flour), F2 (20% carrot flour and 80% wheat flour), F3 (30% carrot flour and 70% wheat flour), and F4 (40% carrot flour and 60% wheat flour). The chemical responses analyzed included moisture content and beta-carotene, while the organoleptic tests evaluated color, aroma, and texture. The results of the study showed that the best treatment for producing dried noodles was F4 (40% carrot flour and 60% wheat flour), with a moisture content of 9.84%, beta-carotene of 216.70 mcg/g, color score of 2.65, aroma score of 3, and texture score of 3.